Digital local information services in developing countries : Evidence from Colombia (2020)
ABSTRACT: this exploratory research identifies and investigates factors that affect the delivery of local information in a developing country. The service provider and 195 local institutions based in Medellin, Colombia collaborate through an online portal, Infolocal, constituting a local information landscape (LIL). The study implements a conceptual framework for the LIL and highlights deficiencies in traditional local information service models. A Delphi study was conducted with global experts of local information services (LIS) in order to refine the traditional Unified Theory of Acceptance and Use of Technology model constructs for the Infolocal information service. Second, a survey was developed based on the revised categories (effort expectancy, performance expectancy, social influence, facilitating conditions, organisational support, and affective commitment) and disseminated to the local institutions to assess their perceptions of the service. This data was then evaluated using exploratory factor analysis. The study found that theories of technology acceptance were insufficient in explaining the disjunctions in the information landscape of this service. This study contributes to closing a gap in understanding the perceptions of LIS practice from the perspective of institutions that engage directly with citizens’ technology acceptance and use behaviour in a multilevel relationship. This article captures, compares, and analyses the disjunctions between the theoretical frameworks as espoused by experts and the practices of LIS.